Peculiarities of carbohydrate and lipid metabolism in infertile patients with clomifen-resistant form of polycystic ovarian syndrome and obesity - Kaminsky, V.; Chaika, V. (Journal of Education, Health and Sport, 2021)
Medical ovulation induction with clomiphene citrate is currently the first line treatment for anovulatory women with PCOS. Clomiphene resistance (failure to ovulate after taking clomiphene) is common, occurring in approximately 15% to 40% of women with PCOS. Resistance is associated with an increased body mass index. The aim of the study was to elucidate the characteristics of carbohydrate and lipid metabolism in patients with clomiphene-resistant PCOS and obesity. Material and methods. A comprehensive examination of 97 infertile patients with PCOS with obesity and clomiphene-resistant PCOS and 46 conditionally healthy normoovulatory women of control group K with 18.5 ≤ body mass index (BMI) < 25 kg/m2, without clinical or biochemical signs of hyperandrogenism, with ovarian volume less than 9 cm3 and without previously known endocrine disease. Clinical-anamnestic, anthropometric, sonographic, immunochemical, enzyme-linked immunosorbent assay, colorimetric, statistical research methods are used. Results and discussion. It was found that the most characteristic features of carbohydrate metabolism disorders in clomiphene-resistant women with PCOS and obesity are increased levels of hypoglycemic index, C-peptide, glucose levels after 2 h in oral glucose tolerance test, HOMA index; and of lipid metabolism - an increase in atherogenic factor, triglycerides, total cholesterol on the background of increased production of leptin and vaspin and decreased secretion of adiponectin, omentin and visfatin.. Conclusions. Visceral obesity plays an important role in the development of insulin resistance and hyperinsulinemia in infertile patients with clomiphene-resistant PCOS and obesity. This category of women in preconception training, before carrying out ovarian drilling or controlled ovarian stimulation, it is necessary to correct disorders of carbohydrate and lipid metabolism.